A rare case of nulliparous prolapse at term - Phool, Divya; Kaur, Khushpreet; Pandove, Arti; Jindal, Ruchi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Uterovaginal prolapse complicating pregnancy is an extremely rare event. Obstetricians should be familiar with the condition as early recognition and close follow up is essential in order to avoid possible fetomaternal risks. Its incidence is higher in women of advanced age and parity. This case report presents a rare occurrence of prolapse in nulliparous woman. In the present case report, we describe a case of a 24 year-old nulliparous female who experienced sudden uterine prolapse at 38 weeks of gestation without labor. She was delivered by cesarean section in view of primi with breech. Following delivery, the prolapse promptly improved and did not recur.